THE DEATH OF ART IN ADORNO'S THEORY OF ANTINOMOUS NATURE OF THE WORKS OF ART - Rūta Marija Marija Vabalaitė (Problemos)
The article deals with the concept of the death of art in Adorno's "Aesthetic Theory". The peculiarity of the concept in comparison with the hegelian one and with traditional interpretations of it consists in that it is to mean the negative relations in the works of art and antinomous nature of art that are the conditions of artistic quality of the work. The concept has meaned the decline of art or the changes of art's essence in its historical transition in traditional theories. Adorno moves the historical transition of art into the particular work of art. The qualities of art must be and not be the characteristic of the very work. Adorno defines an art via its difference from the reality behind the art which is the non-identity of a work to itself. The concept of death is to mean that the work is and is not itself, as it is the function of its other-the historical reality. The condition of non-identity lies in the negative relations among the individual moments of a work and a work as a whole. It is the second meaning of death. The third is an antinomy between thing-like quality and non-material essence of art. The defining quality of art is its difference from the thing, so the reification of art means its death. Meanwhile the objective spirit of art cannot exist but via its form. We consider the concept of objective spirit of art that is immediately subjected neither to the artist, nor to the viewer, nor to the work as a whole, as a principle that constitutes the inherent relations among the parts of a work and the relations of it as a whole to reality behind the particular work of art. The work of art dies as a subjective artefact and stays as an objective truth content in this sense. Adorno does not assert the possibility of an existence of art. He does not assert the indispensable death of art as well. It depends on the existence of the inhuman meaning of nature and if it exists, the existence of art is dependent to the possibility of disclosure of such meaning by the objective spirit of art.